2021
DOI: 10.21272/jnep.13(1).01024
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Photo-Luminescence Emission Using the Line Shape Function for Semiconductor Quantum Dots

Abstract: The outcome of particle size effect on Photoluminescence has been investigated theoretically for CdS, ZnS, CdSe and ZnSe quantum dots. The theory is based on computational modeling in the strong confinement region only where the particle size is less than Bohr's radius. The Photoluminescence emission line shape function which depends on band gap was found to be strongly dependent on particle size. The PL spectra of bulk material is similar for the quantum dots where similar vibronic coupling and normalized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…We observed that value of a ZnS NP is 3.74 eV which is higher than the bulk one (see Figure 8 ) due to surface and size effects in coincidence with Refs. [ 18 , 54 , 60 , 61 , 62 , 63 ]. We will note that, from Equation ( 8 ), it can be seen decreases with increasing the s-d interaction I and increases with increasing the Coulomb interaction v and the electron-phonon interaction , i.e., they are important and must be taken into account in order to observe correct results.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that value of a ZnS NP is 3.74 eV which is higher than the bulk one (see Figure 8 ) due to surface and size effects in coincidence with Refs. [ 18 , 54 , 60 , 61 , 62 , 63 ]. We will note that, from Equation ( 8 ), it can be seen decreases with increasing the s-d interaction I and increases with increasing the Coulomb interaction v and the electron-phonon interaction , i.e., they are important and must be taken into account in order to observe correct results.…”
Section: Resultsmentioning
confidence: 99%